Endogenized Trade Shares in a Global Model - Bernd Meyer; Christian Lutz (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2001)
Globally integrated modelling is achieved by employing trade matrices for linking country models. In the case of COMPASS, this is achieved by having time series for trade matrices of 25 commodity groups linking 53 countries and regions. In addition to country models that are estimated econometrically based on empirical data, trade matrices themselves are available over time in response to changing relative prices (endogenous in the model) and other factors. This paper focuses on an attempt to empirically explain the trade shares.
Keywords: Q4; 330; Endogenized Trade Shares; Global Model; COMPASS; trade matrices